Anomalous temperature dependence of the stationary Josephson tunnel current in junctions between d-wave superconductors - Gabovich, Alexander M.; Voitenko, Alexander I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Stationary Josephson current Ic between d-wave superconductors was calculated for superconductor–insulator–superconductor structures with various rotations of crystals relatively to each other and the junction plane. The directionality of tunneling was taken into account. It was demonstrated that the temperature, T, dependences of Ic can become nonmonotonic for certain electrode orientations due to the T-dependent ratio between the contributions of positive and negative Ic components. This model gives an explanation to the effect observed in junctions involving cuprates and is an alternative to the well-known scenario that makes allowance for Andreev–Saint–James zero-energy levels.